2018
DOI: 10.1177/0192623318804986
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Transcriptome Changes in the ReninAAV db/db uNx Model of Advanced Diabetic Kidney Disease Exhibit Features of Human Disease

Abstract: The ReninAAV db/db uNx model of diabetic kidney disease (DKD) exhibits hallmarks of advanced human disease, including progressive elevations in albuminuria and serum creatinine, loss of glomerular filtration rate, and pathological changes. Microarray analysis of renal transcriptome changes were more similar to human DKD when compared to db/db eNOS À/À model. The model responds to treatment with arterial pressure lowering (lisinopril) or glycemic control (rosiglitazone) at early stages of disease. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 6 publications
6
11
0
Order By: Relevance
“…Accordingly, ReninAAV administration induces persistent hypertension and has recently been shown to accelerate DKD progression in diabetic UNx mice (Harlan, Heinz-Taheny, Sullivan, et al, 2018;Østergaard et al, 2021). Our study corroborates previous findings in the UNx-Renin model, demonstrating biochemical and histological features of progressive DKD, notably severe albuminuria and advanced glomerulosclerosis (Harlan, Heinz-Taheny, Overstreet, et al, 2018;Harlan, Heinz-Taheny, Sullivan, et al, 2018;Østergaard et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Accordingly, ReninAAV administration induces persistent hypertension and has recently been shown to accelerate DKD progression in diabetic UNx mice (Harlan, Heinz-Taheny, Sullivan, et al, 2018;Østergaard et al, 2021). Our study corroborates previous findings in the UNx-Renin model, demonstrating biochemical and histological features of progressive DKD, notably severe albuminuria and advanced glomerulosclerosis (Harlan, Heinz-Taheny, Overstreet, et al, 2018;Harlan, Heinz-Taheny, Sullivan, et al, 2018;Østergaard et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Although several transcriptomic studies have been reported in the db/db UNx and UNx-Renin mouse model, knowledge on disease-associated gene expression changes in these models is based on preselected gene sets Harlan, Heinz-Taheny, Overstreet, et al, 2018;Harlan, Heinz-Taheny, Sullivan, et al, 2018). Consequently, global gene expression profiling could help validating the clinical translatability of these models.…”
Section: Discussionmentioning
confidence: 99%
“…Our study corroborates and extends findings of robust nephroprotective effects of lisinopril in combination with antidiabetic treatment (rosiglitazone) in db/db UNx-ReninAAV mice (20,21).…”
Section: Discussionsupporting
confidence: 89%
“…Induction of persistent hypertension by adeno-associated virus (AAV)-mediated renin gene transfer has recently been reported to exacerbate kidney injury in uninephrectomized (UNx) db/db mice (20,21). Because the db/db UNx-ReninAAV mouse shows close resemblance to human DKD pathogenesis (21), we further validated the model for utility in preclinical drug discovery by characterizing renal disease and outcomes of long-term standard of care using an ACE inhibitor (lisinopril) and SGLT2 inhibitor (empagliflozin).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analysis provides the opportunity to survey changes resulting from genetic, physiological, or environmental interactions that may be involved in CKD pathogenesis [27][28][29]. While proteins show a closer relationship to function, methods analyzing protein quantity and modifications are relatively cumbersome.…”
Section: Gene Expression Analysis Of Kidneys Of Patients With Ckdmentioning
confidence: 99%